PENGEMBANGAN MODEL PEMBELAJARAN AKTIVITAS KEBUGARAN JASMANI MELALUI PERMAINAN LOM-ZIG-LEMBOL (LOMPAT ZIG-ZAG LEMPAR BOLA) PADA SISWA BEKEBUTUHAN KHUSUS BAGIAN B (TUNARUNGU) SLB NEGERI UNGARAN)) (Universitas Negeri Semarang, 2020)
The objective of this study is to describe game model Lom-Zig-Lembol (Jumping Zig-zag Throwing Ball) in learning physical fitness activity for deaf students. This research is the Research and Development (R & D). The following research procedure: 1) the potential and problems, 2) data collection, 3) product design, 4) validation of design (1 expert physical education and 2 learning experts), 5) revised design, 6) test a small scale, 7) revision products, 8) large trial, 9) revision products, 10) which produces a tool of mass-production. The results of the initial product expert validation study obtained an average 88,25% are very good, the result of small-scale trials is 92.50% (excelent). The result of the revision of the expert stated that it was very appropriate to use. The result of large-scale trials is 86.96% (very good). Based on the analysis of research, Lom-Zig-Lembol game (Jumping Zig-zag Throwing Ball) can be used as a teaching model of physical fitness activities on deaf student in schools.